LUNG REGENERATION IN ABSTAINING SMOKERS - Böhm, Radoslav; Sedlák, Antonín; Bulko, Martin; Holý, Karol (Radiation protection dosimetry, 2019)
Smoking modifies morphological and physiological parameters of the lungs. Due to the irritation of airways, the natural self-cleaning ability of the lungs is impaired. The mucus accumulates in the airways and various infections develop, leading to chronic bronchitis. After the cessation of smoking, the lungs of the smoker start to heal and regenerate. Cilia in the lungs start to grow again and cleanse the lungs, thus reducing the risk of infection. The regeneration of the lungs takes a long time and depends on the degree of lung damage due to smoking. The aim of this study was to reconstruct the evolution of this regeneration process in chronic smokers by using the biological effects of radon and its decay products. Thus, radon in this study served as a tracer of changes induced by smoking.
Keywords: plíce; radon; biologické modely; regenerace; kouření; Computer Simulation; Radon; lidé; Smoking; Models, Biological; obstrukční plicní nemoci; Lung; Regeneration; počítačová simulace; Lung Diseases, Obstructive; Humans